Operative choice for subtrochanteric femoral fracture in school-aged children: Triple elastic stable intramedullary nail versus locking plate - Hong, Pan; Zhao, Xiaolong; Ze, Renhao; Rai, Saroj; Liu, Ruikang; Li, Jin; Tang, Xin (Frontiers in Pediatrics, 2022)
Background The management strategy of subtrochanteric fractures remains controversial, and triple elastic stable intramedullary nail (ESIN) has not been reported for pediatric subtrochanteric fractures. This study aimed to compare the clinical effects of treating school-aged children with subtrochanteric fractures with triple ESINs versus locking plates. Methods We conducted a retrospective review of pediatric patients with subtrochanteric femoral fracture receiving either triple ESINs (TE) or locking plates (LPs) between January 2010 and January 2018. Sixteen patients in each group with matched age, sex, and fracture characteristics were included in the study. The preoperative data, including baseline information of the patients, fracture pattern, and types of surgical procedure, were collected from the hospital database. Patients were followed-up at the outpatient clinic in the 3rd month, 6th month, 12th month, and annually afterward. Hardware removal was performed at 9 – 18 months after the primary surgery. Results In all, 16 patients (8.4 ± 1.5-year-old, 7 boys, 9 girls) in the TE group and 16 patients (8.4 ± 1.4-year-old, 7 boys, 9 girls) in the LP group were included. There was significantly less operative time, reduced estimated blood loss, and shortened hospital stay for the TE as compared with the LP (P < 0.001). However, higher fluoroscopy frequency was observed in the TE group than in the LP group (P < 0.001). The time to union was faster in the TE group than in the LP group (P = 0.031). However, the angulation was higher in the TE group (3.2 ± 0.6) than the LP group (1.8 ± 0.5), and the incidence of implant prominence was higher in the TE group (7/16, 43.8%) than the LP group (1/16, 6.3%). Conclusion Compared with the locking plates, triple ESINs demonstrated significantly less operative time, reduced estimated blood loss, and shortened hospital stay. Besides, both TE and LP groups produced satisfactory outcomes in school-aged children with subtrochanteric fractures. Therefore, TE remains a feasible choice for subtrochanteric fractures in school-aged children.